Isolation of Enterococcus faecium and determination of its mechanism for promoting the growth and development of Drosophila - Li, Yujuan; Pan, Lei; Li, Pengcheng; Gao, Fuguo; Wang, Lei; Chen, Jian; Li, Zhichao; Gao, Yongheng; Gong, Yumei; Jin, Faguang (Scientific Reports, 2023)
Intestinal symbiotic microorganisms have a strong capacity to regulate the physiological functions of their host, and Drosophila serves as a useful model. Enterococcus faecium (E. faecium) is a member of the normal intestinal flora of animals. Lactic acid bacteria (LAB) such as E. faecium can promote the growth and development of Drosophila, but the mechanism of regulation of Drosophila is poorly understood. In this study, we found that E. faecium used a carbon source to produce probiotic acids. E. faecium is a symbiotic bacterium for Drosophila, and adult flies passed on parental flora to offspring. E. faecium promoted the growth and development of Drosophila, especially under poor nutritional conditions. E. faecium shortened the developmental process for Drosophila and accelerated the transformation from larva to pupa. Finally, E. faecium promoted the growth and development of Drosophila through TOR and insulin signalling pathways.
CRIS-Team Scopus Importer:2023-11-17